Character Based Leadership In Quality Improvement Managerial At The Naval Command And Staff College Unit - Manahan Budiarto Pandjaitan , Manahan; Moh. Khusaini, Moh.; Panji Suwarno, Panji (CV. AFDIFAL MAJU BERKAH, 2024)
Leaders may be identified by their particular habits, disposition, character, and personality, which allow them to stand out from the crowd in terms of conduct and style. His conduct and style of leadership will undoubtedly be influenced by this way of living. The ability to inspire others to alter their views in order to conform to the goals and will of the leader is known as leadership, or the creative moral power. In the Seskoal Unit, leadership has inherent value in assessing and evaluating members of their unit for their performance in addition to issuing commands to subordinates. A competent leader would constantly inspire their followers to operate in accordance with Indonesian standards and regulations, using a leadership approach that incorporates local knowledge. The goal of this study is to clarify the leadership approach used by Seskoal leaders in order to raise unit performance. The research methodology used is a qualitative approach employing a descriptive technique, which is the process of creating and researching scientific publications by thoroughly describing the problem's topic and investigating data sources that are pertinent to the issues raised by the literature reviews. The assessment concludes that the Seskoal Unit commanders' leadership style focuses two strategies: commanding subordinates in addition to provide inspiration and assessment.